Evaluasi Pembangkit Listrik Tenaga Angin Kecepatan Rendah Sebagai Penggerak Refrigerator Es 300 Kg/Hari Untuk Nelayan - Adi Saputra Ismy; Ahmad Syuhada; - Hamdani (Jurnal Teknik Mesin Unsyiah, 2012)
Generally, the fishermen in the fishing village of Lancang only 20 trips/month of the year. The average total amount of ice required for the first type of fishing boat is 300 kg ice/day and 150 kg of ice/day for both types of fishing vessels. So, based on the total number of observations of ice demand data is 9000 kg/month (300 kg ice/day). One solution that can be taken is the utilization of wind energy resources owned by the village to generate electrical energy as the driving engine refrigerator. Methods of research conducted in three phases, the first stage is filled with wind potential measurement, processing and analysis of wind speed data. In the second stage of the development of modeling performed to evaluate the performance of Genesis turbines based on the data load and wind potential. The third stage is filled with measurements of 10 KW wind turbine performance and then made ​​comparisons with modeling results. From the analysis of wind speed data obtained from the measurement results obtained by the average wind speed reaches the village of Lancang 3-5 m/s at a height of 15 m above sea level. Based on analytical results obtained using the software Homer wind turbine energy production is 7.474 kWh/year and the results of measurements of overall performance of the turbine can be concluded that wind turbines are the object of study is only able to deliver an average power 3-7 KW.